The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0378-4371(02)01662-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence in the sea surface temperature fluctuations

Abstract: We study the temporal correlations in the sea surface temperature (SST) fluctuations around the seasonal mean values in the Atlantic and Pacific oceans. We apply a method that systematically overcome possible trends in the data. We find that the SST persistence, characterized by the correlation C(s) of temperature fluctuations separated by a time period s, displays two different regimes. In the short-time regime which extends up to roughly 10 months, the temperature fluctuations display a nonstationary behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
100
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 23 publications
14
100
2
5
Order By: Relevance
“…Thus, the net result drawn is that the difference between the scaling exponents in both sea and land contributions to the surface air temperature stems mainly from the sea surface temperature (SST), which exhibits stronger scaling in the Southern than in the Northern Hemisphere. This finding is in line with that of Monetti et al (2003), according to which a stronger persistence is observed over the oceans (Atlantic and Pacifc Oceans) than over the continents. Scaling in SST up to decades was also demonstrated in observations and coupled atmosphereocean models with complex and mixed-layer oceans by Fraedrich and Blender (2003) and others (e.g., Ausloos and Ivanova, 2001;Eichner et al, 2003).…”
Section: Dfa Exponent In the Time Series Of The Monthly Mean Lsat Anosupporting
confidence: 91%
“…Thus, the net result drawn is that the difference between the scaling exponents in both sea and land contributions to the surface air temperature stems mainly from the sea surface temperature (SST), which exhibits stronger scaling in the Southern than in the Northern Hemisphere. This finding is in line with that of Monetti et al (2003), according to which a stronger persistence is observed over the oceans (Atlantic and Pacifc Oceans) than over the continents. Scaling in SST up to decades was also demonstrated in observations and coupled atmosphereocean models with complex and mixed-layer oceans by Fraedrich and Blender (2003) and others (e.g., Ausloos and Ivanova, 2001;Eichner et al, 2003).…”
Section: Dfa Exponent In the Time Series Of The Monthly Mean Lsat Anosupporting
confidence: 91%
“…[2] In the past decade it has been recognized that multidecadal temperature records are long-term correlated [Koscielny- Bunde et al, 1996;Pelletier and Turcotte, 1997;Koscielny-Bunde et al, 1998;Talkner and Weber, 2000;Weber and Talkner, 2001;Eichner et al, 2003;Monetti et al, 2003;Király et al, 2006], with a correlation exponent g ' 0.7 for continental and coastline regions, and g in a broad range around 0.4 for marine regions.…”
Section: Introductionmentioning
confidence: 99%
“…temperatures, relative humidity, wind, atmospheric general circulations, etc.) were found to be characterized by LTM (Koscielny- Bunde et al 1998;Eichner et al 2003;Monetti et al 2003;Kantelhardt et al 2006;Chen et al 2007;Rybski et al 2008;Vyushin and Kushner 2009;Feng et al 2009;Franzke 2010;Dangendorf et al 2014;Massah and Kantz 2016). As the name implies, LTM measures the connections of climate states observed at different time points.…”
Section: Introductionmentioning
confidence: 99%